2008
DOI: 10.1007/s00421-008-0731-9
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the respiratory mechanical and muscle function of competitive breath-hold divers

Abstract: Competitive breath-hold divers (BHD) employ glossopharyngeal insufflation (GI) to increase intrapulmonary oxygen stores and prevent the lungs from dangerous compressions at great depths. Glossopharyngeal insufflation is associated with inflation of the lungs beyond total lung capacity (TLC). It is currently unknown whether GI transiently over-distends the lungs or adversely affects lung elastic properties in the long-term. Resting lung function, ventilatory drive, muscle strength, and lung compliance were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 19 publications
1
34
1
3
Order By: Relevance
“…In contrast to our results, many researchers have observed a decline in FEV 1 [9,[10][11][12] and FVC in divers [8,9,11,12]. Of these studies, only Tetzllaf et al [3] evaluated pulmonary function in free divers who, because they had competitive goals, dived to depths greater than the subjects in the present study. The other studies evaluated commercial scuba divers breathing a mixture of gases under hyperbaric conditions, a situation quite different from breath-hold diving.…”
Section: Lung Function In Breath-hold Diving Fishermen O R I G I N a contrasting
confidence: 97%
See 4 more Smart Citations
“…In contrast to our results, many researchers have observed a decline in FEV 1 [9,[10][11][12] and FVC in divers [8,9,11,12]. Of these studies, only Tetzllaf et al [3] evaluated pulmonary function in free divers who, because they had competitive goals, dived to depths greater than the subjects in the present study. The other studies evaluated commercial scuba divers breathing a mixture of gases under hyperbaric conditions, a situation quite different from breath-hold diving.…”
Section: Lung Function In Breath-hold Diving Fishermen O R I G I N a contrasting
confidence: 97%
“…Tetzllaf et al [3] found no effect of diving on MIP in their assessment of mechanical characteristics and respiratory function when comparing competitive free divers, scuba divers and controls.…”
Section: Lung Function In Breath-hold Diving Fishermen O R I G I N a mentioning
confidence: 96%
See 3 more Smart Citations